Progress Report on the Activities of the Independent Evaluation Office (IEO). (Policy Papers; Policy Paper, 2007)
Since its last Report to the IMFC in Singapore, the IEO has focused most of its attention on completion of two evaluations; namely the IMF and Aid to Sub-Saharan Africa and the IMF's Advice on Exchange Rate Policy. In addition work is progressing or has been initiated on a number of new topics identified in the last Report.